1987
DOI: 10.1159/000146438
|View full text |Cite
|
Sign up to set email alerts
|

The Rete Testis of the Goat, a Morphological Study

Abstract: The rete testis of the goat can be divided into three parts, septal, mediastinal and extratesticular. The septal rete is short, relatively straight and connects the terminal part of the seminiferous tubules with the mediastinal rete. The mediastinal rete is a labyrinth of intercommunicating channels that occupies about two-thirds of the central axis of the testis. The extratesticular rete is located outside the testis at its extremitas capitata and forms sac-like dilations up to 2 mm in diameter. The rete test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Septal segments of rete tubules as those recorded in goat, bovines and cat were demonstrated in the present study [7,8,10]. These septal segments connect the terminal parts of the seminiferous tubules with the mediastinal rete [7].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Septal segments of rete tubules as those recorded in goat, bovines and cat were demonstrated in the present study [7,8,10]. These septal segments connect the terminal parts of the seminiferous tubules with the mediastinal rete [7].…”
Section: Discussionsupporting
confidence: 77%
“…These septal segments connect the terminal parts of the seminiferous tubules with the mediastinal rete [7]. In our opinion, the septal rete tubules represent a pathway for the drainage of the testicular lobules that have no direct contact with the mediastinum testis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Orsi et al (1984) identified mediastinal part of rete testis in goats, the former yielded by union of seminiferous tubules while the latter were the large straight inter connecting canals as observed in the present study. Goyal & Williams (1987) observed three segments of rete testis in American goats i.e. septal, mediastinal and extra-testicular.…”
Section: Discussionmentioning
confidence: 89%
“…While the morphology of the septal and mediastinal rete has been studied in depth in various species, including rats (Roosen-Runge, 1961;Leeson, 1962;Dym, 1976;Hermo and Dworkin, 19881, guinea pigs (Ladman and Young, 1958;Vitale-Calpe and Aoki, 1969;Fawcett and Dym, 1974), bulls (Sinowatz et al, 1979;Wrobel et al, 1978;Goyal, 19821, goats (Ezeasor, 1986;Goyal and Williams, 1987), horses (Amann et al, 1977), monkeys (Burgos et al, 1979), and man (Bustos-Obregon and Holstein, 1976;Roosen-Runge and Holstein, 1978;Lindner, 1982), similar information about the extratesticular rete is scarce. To our knowledge, the morphology of the extratesticular rete has been clearly illustrated only in man (Roosen-Runge and Holstein, 1978) and to some extent in the goat (Goyal and Williams, 1987). Even in these species, information on the topography and junctional relationships with the ductuli efferentes is lacking.…”
mentioning
confidence: 99%